2020
DOI: 10.3390/catal10091071
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Dimethyl Ether from Syngas on Bifunctional Hybrid Catalysts Based on Supported H3PW12O40 and Cu-ZnO(Al): Effect of Heteropolyacid Loading on Hybrid Structure and Catalytic Activity

Abstract: The performance of bifunctional hybrid catalysts based on phosphotungstic acid (H3PW12O40, HPW) supported on TiO2 combined with Cu-ZnO(Al) catalyst in the direct synthesis of dimethyl ether (DME) from syngas has been investigated. We studied the effect of the HPW loading on TiO2 (from 1.4 to 2.7 monolayers) on the dispersion and acid characteristics of the HPW clusters. When the concentration of the heteropoliacid is slightly higher than the monolayer (1.4 monolayers) the acidity of the clusters is perturbed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 75 publications
1
15
1
Order By: Relevance
“…Activity tests were performed in a fixed-bed reactor loaded with hybrid catalysts diluted with SiC (1:3 vol). The overall methanol and DME yield on CZA-HPW/Ti hybrids was, in all cases, lower than the methanol yield achieved on the CZA reference [141].…”
Section: Core Catalystcontrasting
confidence: 55%
“…Activity tests were performed in a fixed-bed reactor loaded with hybrid catalysts diluted with SiC (1:3 vol). The overall methanol and DME yield on CZA-HPW/Ti hybrids was, in all cases, lower than the methanol yield achieved on the CZA reference [141].…”
Section: Core Catalystcontrasting
confidence: 55%
“…The enhancement of activity of TiO 2 -supported HPA was associated with the good dispersion of H 3 PW 12 O 40 units on the TiO 2 surface, allowing easy access of methanol to the active acid sites. We have recently investigated H 3 PW 12 O 40 supported on TiO 2 combined with Cu/ZnO­(Al) catalyst as an active bifunctional catalyst for the direct synthesis of DME from syngas . The activity of this bifunctional catalyst was remarkably superior to that of the state-of-the-art Cu–ZnO­(Al)/HZSM-5 bifunctional catalyst commonly employed for DME production.…”
Section: Introductionmentioning
confidence: 99%
“…At this optimum loading, both HPW and HSiW were well dispersed onto the support surface, permitting the easy access of methanol to the active acid sites. The effect of supporting tungstophosphoric acid (H 3 PW 12 O 40 , HPW) on TiO 2 on the activity of a hybrid catalyst containing Cu-ZnO(Al) and HPW/TiO 2 as metal and acid functions, respectively, was investigated recently in the direct CO 2 hydrogenation to DME [122]. In good agreement with the study by Ladera et al [123], it was found that the amount of HPW employed for TiO 2 modification should be optimized.…”
Section: Heteropolyacids (Hpas)-based Catalystsmentioning
confidence: 58%
“…Noticeably, the activities of this catalyst was higher than that of the reference hybrid Cu-ZnO(Al)/HZSM-5 catalyst, typically employed for DME production. However, the catalyst modified with an optimized amount of HPW exhibited some kind of catalyst deactivation under the reaction conditions employed [122].…”
Section: Heteropolyacids (Hpas)-based Catalystsmentioning
confidence: 99%